A Maple Code to Perform Operations on Single Valued Neutrosophic Matrices - Said Broumi; Mohamed Bisher Zeina; M. Lathamaheswari; Assia Bakali; Mohamed Talea (Neutrosophic Sets and Systems, 2022)
In this paper, we present a maple programming code that helps useres and scientific researchers to input single valued neutrosophic matrices, checks whether inputted matrix is single valued neutrosohic matrix, finds the complement of a single valued neutrosophic matrix, calculates score matrix, accuracy matrix and certainty matrix, finds the union and intersection of two single valued neutrosophic matrices, finds addition and product of two single valued neutrosophic matrices, also finds transpose of single valued neutrosophic matrix. This code is very important and useful in decision making problems that depend on single valued neutrosophic data.